Bioenergy perspectives of cattails biomass cultivated from municipal wastewater via hydrothermal liquefaction and hydro-deoxygenation. (15th January 2021) - Arun, Jayaseelan; Gopinath, Kannappan Panchamoorthy; Sivaramakrishnan, Ramachandran; Madhav, Nagarajan Vikas; Abhishek, Krishnan; Ramanan, Vijaya Gurumurthy Karthik; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Bio oil was obtained from the cattail biomass grown in wastewater. Liquefaction experiments produced 32.4 wt% of bio-oil with HHV of 29.88 MJ/kg. The deoxygenation efficiency of carbon-supported catalyst was used in HDO process. HDO process the upgraded bio-oil yield was 24.1 wt% with HHV of 37.63 MJ/kg. Cattail biomass is promising for the bio-oil production and wastewater treatment. Abstract: This study targets the value addition of cattails biomass cultivated from wastewater through hydrothermal liquefaction (HTL) and Hydro-deoxygenation (HDO) process in presence of carbon supported catalyst. Cattails biomass for bio-oil production was cultivated from wastewater through advanced phyto-rid technology (AP-RT). Liquefaction experiments produced 32.4 wt% of bio-oil with HHV of 29.88 MJ/kg for 15 g of biomass at a temperature of 300 ℃ at a reaction time of 60 min. Activated carbon (rice husk) supported niobium catalyst was produced via wet impregnation method. The deoxygenation efficiency of carbon-supported catalyst (0–5 wt%) was studied in HDO process. From the HDO process the upgraded bio-oil yield was 24.1 wt% with deoxygenation degree of 75% for catalyst load (3 wt%) with HHV of 37.63 MJ/kg. Approximately 1.17 g of deoxygenated bio-oil was obtained from 15 g of biomass. Gas Chromatographic and Mass Spectroscopic (GC–MS) analysis showed hydrocarbons content of 28% in HTL and 38% in HDO bio-oil with reduced oxygenates. The carbon supported catalysts in reusability studies showed deoxygenation percentage of 56% and carbon recovery of 81% at the end of 4th cycle.